NATIONAL-CULTURAL CONNOTATIONS OF COLOR-RELATED PHRASEOLOGICAL UNITS IN ENGLISH AND RUSSIAN - Atajanova Jamila Akram qizi; Seytimbetova Aykumar Pulatbaevna (Western European Studies, 2025)
This article explores the national-cultural semantics of color-based phraseological units in English and Russian. It argues that the study of idioms requires more than structural or lexical analysis; a deeper cultural and symbolic perspective is necessary to understand how colors shape metaphorical meaning. Through a comparative examination of color idioms, this work highlights the role of cultural memory, emotional association, and societal perception embedded in language. While certain symbolic uses of color display universal tendencies, others diverge sharply, revealing unique facets of Russian and English worldviews.
Keywords: Russian; emotional; perception; symbolic